3(3n+2)=9(4n+5)+8

Simple and best practice solution for 3(3n+2)=9(4n+5)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3n+2)=9(4n+5)+8 equation:


Simplifying
3(3n + 2) = 9(4n + 5) + 8

Reorder the terms:
3(2 + 3n) = 9(4n + 5) + 8
(2 * 3 + 3n * 3) = 9(4n + 5) + 8
(6 + 9n) = 9(4n + 5) + 8

Reorder the terms:
6 + 9n = 9(5 + 4n) + 8
6 + 9n = (5 * 9 + 4n * 9) + 8
6 + 9n = (45 + 36n) + 8

Reorder the terms:
6 + 9n = 45 + 8 + 36n

Combine like terms: 45 + 8 = 53
6 + 9n = 53 + 36n

Solving
6 + 9n = 53 + 36n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-36n' to each side of the equation.
6 + 9n + -36n = 53 + 36n + -36n

Combine like terms: 9n + -36n = -27n
6 + -27n = 53 + 36n + -36n

Combine like terms: 36n + -36n = 0
6 + -27n = 53 + 0
6 + -27n = 53

Add '-6' to each side of the equation.
6 + -6 + -27n = 53 + -6

Combine like terms: 6 + -6 = 0
0 + -27n = 53 + -6
-27n = 53 + -6

Combine like terms: 53 + -6 = 47
-27n = 47

Divide each side by '-27'.
n = -1.740740741

Simplifying
n = -1.740740741

See similar equations:

| 6x+y=98 | | -40-2b=-2+2(1-5b) | | 56=4x | | w^25= | | A(x-2)(x-3)= | | 2+m=-10 | | 6x+9=-108-7x | | -8q-3(q+4)=q+7 | | 6x+9=-1008-7x | | x-(-3)=-1 | | -4y-13=9y+13 | | -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x |

Equations solver categories